The potential of 15N metabolic labeling for schizophrenia research (Archives of Clinical Psychiatry, 2013)
Psychiatric research is in need of non-hypothesis driven approaches to unravel the neurobiological underpinnings and identify molecular biomarkers for psychiatric disorders. Proteomics methodologies constitute a state-of-the-art toolbox for biomarker discovery in psychiatric research. Here we present the principle of in vivo 15N metabolic labeling for quantitative proteomics experiments and applications of this method in animal models of psychiatric phenotypes, with a particular focus on schizophrenia. Additionally we explore the potential of 15N metabolic labeling in different experimental set-ups as well as methodological considerations of 15N metabolic labeling-based quantification studies.